Inhibition of spleen tyrosine kinase activation ameliorates inflammation, cell death, and steatosis in alcoholic liver disease. Issue 4 (22nd July 2016) - Bukong, Terence N.; Iracheta‐Vellve, Arvin; Saha, Banishree; Ambade, Aditya; Satishchandran, Abhishek; Gyongyosi, Benedek; Lowe, Patrick; Catalano, Donna; Kodys, Karen; Szabo, Gyongyi
Abstract : The spectrum of alcoholic liver disease (ALD) is a major cause of mortality with limited therapies available. Because alcohol targets numerous signaling pathways in hepatocytes and in immune cells, the identification of a master regulatory target that modulates multiple signaling processes is attractive. In this report, we assessed the role of spleen tyrosine kinase (SYK), a nonreceptor tyrosine kinase, which has a central modulatory role in multiple proinflammatory signaling pathways involved in the pathomechanism of ALD. Using mouse disease models that represent various phases in the progression of human ALD, we found that alcohol, in all of these models, induced SYK activation in the liver, both in hepatocytes and liver mononuclear cells. Furthermore, significant SYK activation also occurred in liver samples and peripheral blood mononuclear cells of patients with ALD/alcoholic hepatitis compared to controls. Functional inhibition of SYK activation in vivo abrogated alcohol‐induced hepatic neutrophil infiltration, resident immune cell activation, as well as inflammasome and extracellular signal‐regulated kinase 1 and 2‐mediated nuclear factor kappa B activation in mice. Strikingly, inhibition of SYK activation diminished alcohol‐induced hepatic steatosis and interferon regulatory factor 3‐mediated apoptosis. Conclusion : Our data demonstrate a novel, functional, and multicellular role for SYK phosphorylation in modulating immune cell‐driven liver inflammation, hepatocyte cell death, and steatosis at different stages of ALD. These novel findings highlight SYK as a potential multifunctional target in the treatment of alcoholic steatohepatitis. (Hepatology 2016;64:1057‐1071)